Pelatihan Penulisan Penelitian Tindakan Kelas Bagi Guru - R Rahmatullah; I Inanna (Universitas Muhammadiyah Parepare)
This training aims to provide teachers with an understanding of the importance of classroom action research, as an effort to improve the process and quality of learning in schools. This activity was carried out in the form of classroom action research writing training which lasted for (2) two days starting on 29-30 September 2017. The material presented consisted of 2 (two) main themes namely the basic concepts of classroom action research and practical exercises for writing classroom action research. The number of participants who attended the training was 29 teachers. Methods of delivering training materials consist of lecture, question and answer, discussion and drill methods. The results of the training show that the understanding and mastery of the material on Classroom Action Research for participants has increased after attending the training compared to before. In addition, the trainees already have the skills and abilities to make Classroom Action Research Proposals as well as high motivation in participating in training activities.